A complete and continuous core record of deep-water mass transport deposits - Cheng, Cong; Jiang, Tao; Kuang, Zenggui; Ren, Jinfeng; Chen, Zigui; Zhao, Xu; Rahman, Maqsood Ur; Ning, Fulong (Frontiers in Marine Science, 2025)
Mass transport deposits are a fundamental component of deep-water sedimentary systems and play a crucial role in the transportation of sediments from continental slopes to deep-sea basins. However, there exists a significant gap in our understanding of their internal vertical structure, core facies characteristics, and associated sedimentary processes. This study employs comprehensive and continuous core data, logging-while-drilling data, and high-resolution 3D seismic data obtained from the Qiongdongnan Basin in the northern South China Sea to meticulously delineate the core facies of deep-water sedimentary systems within the investigated area. Among these findings, eleven core facies types have been summarized and categorized across all identified sedimentary systems. These include mass transport deposits, turbidity currents, bottom currents, as well as hemipelagic and pelagic deposits. Mass transport deposits display a range of deformation characteristics within their cores, including slumps and debris flows. Their internal structure encompasses various sedimentation processes that involve not only turbidity currents but also hemipelagic and pelagic deposits. This study further explores the issue of phase division in mass transport deposits across various dataset scales, including core, log, and seismic data. It proposes new insights into sedimentary processes and patterns for mass transport deposits in deep-water environments while examining their dynamic interactions with gas hydrates. Additionally, this study summarizes the overall framework of deep-water sedimentary systems present in the Qiongdongnan Basin. The aim is to provide geological insights that will inform future studies on mass transport deposits.